An Empirical Evaluation of the Relationship between Trade Openness and External Debt: Turkish Case - Ozlem Ayvaz Kizilgol; Evren Ipek (International Econometric Review (IER), 2014)
This paper aims to analyze the empirical relationship between trade openness and external debt for the Turkish economy, using quarterly time series data from the 1990:1-2012:2 periods. We utilize the bounds testing procedure to establish the cointegration relationship among variables and the ARDL analysis to detect short run and log run static effects. We support the results from the ARDL model through the application of GMM estimation, achieved with different model definitions. Empirical results indicate that increasing trade openness affects external debt positively in both the short run and long run.
Keywords: F34; F13; C22; 330; Foreign Debt; Openness; ARDL; GMM